Linear and multi-arm functionalizable polymeric constructs for targeted drug delivery and imaging applications - Gök, Özgül. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Multifunctional polymers with different architectures were designed as macromolecular carriers for drug delivery and imaging applications. To this end, linear and multiarm copolymers incorporated with reactive groups were synthesized. The first study outlines the design of a thiol-reactive water soluble maleimide-based copolymer that can be utilized for targeted delivery system. Water soluble thiol-reactive linear copolymers were conjugated with a thiol-containing hydrophobic fluorescent dye and a peptide based targeting group. In vitro studies over both cancerous and healthy cells demonstrated non-toxicity of the polymeric carrier and enhanced uptake for polymers containing the targeting group. The second project involves the synthesis of polymer-drug conjugates where a chemotherapy drug was attached to linear polymers. These were investigated for in vitro cytotoxicity and in vivo pharmacokinetic profiles to demonstrate benefits of drug conjugation to polymers. The third project involves development of polymers containing clusters of functional groups as side chains at precise location along the polymer backbone. Linear copolymers of styrene and maleimide containing polyester dendrons were synthesized via nitroxide-mediated radical polymerization. Successful incorporation of dendrons containing alkene units was undertaken and these were modified with thiol-containing molecules. Fourth part of thesis focuses on the design of orthogonally reactive multiarm star polymers as drug delivery vehicles. Polyester dendrons containing initiators were designed to obtain multiarm copolymers. Obtained copolymers contained thiol reactive maleimide group at the core and activated esters along the polymeric arms. These copolymers were efficiently conjugated with a hydrophobic fluorescent dye at the core and an anti-cancer drug gemcitabine along the side chains. In vitro studies over cancerous cells displayed the reduced toxicity of drug upon polymer conjugation. Final project outlines the design of multiarm water soluble polymers containing a pyridyl disulfide based reversible linker for conjugation of peptides and small molecules. In summary, various linear and multiarm functional polymers were designed for facile conjugation of drugs, imaging and targeting groups to fabricate ideal drug delivery systems.
Keywords: Biomedical materials.; Polymers.